Exogenous Carbohydrate Reduces Cortisol Response from Combined Mental and Physical Stress - McAllister, M. J.; Webb, H. E.; Tidwell, D. K.; Smith, J. W.; Fountain, B. J.; Schilling, M. W.; Williams, R. D., Jr. (International Journal of Sports Medicine, 2016)
Combined mental and physical stress is associated with exacerbated cortisol production which may increase risk for the progression of cardiovascular disease in individuals working in high-stress occupations (e.g., firefighters, military personnel, etc.). Carbohydrate (CHO) ingestion prior to physical stress may attenuate cortisol concentrations. This project was the first to investigate the effect of CHO ingestion on cortisol response from combined mental and physical stress. 16 men 21–30 years old were randomly assigned a 6.6% CHO beverage or non-CHO control 15 min prior to performing a dual-concurrent-stress challenge. This consisted of physical stress (i.e., steady state exercise) combined with computerized mental challenges. Blood was sampled 70, 40, and 15 min before exercise, immediately at onset of exercise, 10, 20, 30, 35 min during exercise, and 15, 30, 45, and 60 min after exercise. There was a significant main effect for treatment regarding mean cortisol concentrations (F=5.30, P=0.0219). The total area under curve for cortisol was less when CHO was ingested (T7=4.07, P=0.0048). These findings suggest that CHO ingestion immediately prior to combined mental and physical stress may attenuate cortisol responses.
Keywords: glucose; exercise; stressor; cardiovascular